Characteristics of Benighat group in the context of geological framework of Gorkha - Mugling area and the southern Chure range - Adhikary, T. P. (Journal of Nepal Geological Society, 1991)
A separate Benighat group is suggested for the Upper Nawakot Group, occupying the core of the Mahabharat syncline in the Gorkha-Mugling area. Lower Nawakot Group is also divided into two lithologically ahd structurally distinct groups, Dhading& Kunchha. Benighat Group is an assemblage of alternating calcareous and argillaceous rock units. Six mappable units are distinguished, viz. Hushdi Beds, Dhungre Slates, Jogimara Limestone, Sairling Phyllites, Malekhu Limestone and Robang Phyllites. Basic rocks are found to occur in the upper and middle parts of the Benighat Group.